1996
DOI: 10.1128/jvi.70.1.373-382.1996
|View full text |Cite
|
Sign up to set email alerts
|

Multiple regulatory events influence human cytomegalovirus DNA polymerase (UL54) expression during viral infection

Abstract: The human cytomegalovirus (HCMV) DNA polymerase gene (UL54; also called pol) is a prototypical early gene in that expression is mandatory for viral DNA replication. Recently, we have identified the major regulatory element in the UL54 promoter responsive to the major immediate early (MIE) proteins (UL122 and UL123) (J. A. Kerry, M. A. Priddy, and R. M. Stenberg, J. Virol. 68:4167-4176, 1994). Mutation of this element, inverted repeat sequence 1 (IR1), abrogates binding of cellular proteins to the UL54 promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
47
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 57 publications
5
47
0
1
Order By: Relevance
“…Moreover, either or both of these could occur at any step in the series of events controlling protein accumulation. In this regard, we note that UL112-113-mediated activation of the UL54 promoter depends upon activation by MIE proteins mediated through the IR1 element, whether or not the UL112-113 proteins are expressed constitutively (30).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Moreover, either or both of these could occur at any step in the series of events controlling protein accumulation. In this regard, we note that UL112-113-mediated activation of the UL54 promoter depends upon activation by MIE proteins mediated through the IR1 element, whether or not the UL112-113 proteins are expressed constitutively (30).…”
Section: Discussionmentioning
confidence: 88%
“…Thus, we might have overlooked the apparent role of this region in regulating early gene expression if we had used simpler experimental designs; these results underscore the power of transient complementation in dissecting complex processes. However, UL112-113 did activate the UL54 promoter in combination with MIE when transfected under slightly different conditions (30).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This protein is synthesized only in the presence of viral IE antigens, and has been shown to increase the activity of viral DNA polymerase that is the major beta cascade protein [Ertl and Powell, 1992]. It has been shown that multiple regulatory events affect DNA polymerase expression and is dependent upon the co-operative regulatory interactions of viral and cellular proteins Kerry et al, 1996]. When agarose was layered on cultures infected with a low virus dose, the production of all antigens at Day 7 was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of pIRS1 (846 amino acids [aa], 91 kDa) and pTRS1 (788 aa, 84 kDa) function have demonstrated that one of the two open reading frames is required for transient complementation of oriLyt-dependent viral DNA synthesis (21,22) and that the irs1 region is not essential for viral replication, as a deletion of this region did not appreciably change the pattern of viral growth in permissive cell lines (13). Transactivating properties of pIRS1 and pTRS1 were investigated in cotransfection experiments (11,14,26). Plasmids containing the irs1 and trs1 genes upregulated the activity of the late ICP36 promoter in the presence of the viral IE1 and IE2 proteins but did not transactivate it when transfected alone (26).…”
mentioning
confidence: 99%